ANALYSIS OF CLIMATOLOGICAL THERMAL COMFORT IN DKI JAKARTA USING HEAT INDEX (HUMIDEX) - Trinah Wati; Riri Indriani Nasution (Pusbindiklat - LIPI, 2018)
Interactions between human and environment about the influence of the physical atmosphere’s state or weather on human is expressed in com- fort level. The complex relationship between health and weather factors with human comfort is defined as biometeorological index. One of the biometeorological indices is heat index called as Humidex. Studies about Humidex in Jakarta were conducted using climate data stations of Indonesian Agency for Meteorology, Climatology and Geophysics (BMKG), namely air temperature, relative humidity and wind speed daily average during 1985 to 2012. The purpose of this study was to determine the level of thermal comfort using heat index Humidex in Jakarta and its climatological trends during 1985 to 2012. Comparative analysis between Humidex and the wind speed and also with the number of vehicles in Jakarta were conducted to determine their impact to the heat index in Jakarta. The results showed that the Humidex monthly average in Jakarta ranged between 36,1 °C and 39,5 °C. Humidex monthly pattern had two peaks with the first peak was on May and the second one was on November, while the lowest value was recorded on August and January. Humidex in Jakarta tended to increase between 0.05 °C and 0.08 °C with its coefficient of determination (R2) was between 0.36 and 0.71. The effect of wind speed to Humidex was lowering the value of Humidex which increased the thermal comfort. Meanwhile, the number of vehicles showed a tendency to grow exponentially, which affected the further decline in thermal comfort level in Jakarta.